Comparing the Efficacy of Eletriptan for Migraine in Women During Menstrual and Non‐Menstrual Time Periods: A Pooled Analysis of Randomized Controlled Trials. Issue 2 (29th October 2013) - Bhambri, Rahul; Martin, Vincent T.; Abdulsattar, Younos; Silberstein, Stephen; Almas, Mary; Chatterjee, Anjan; Ramos, Elodie
<x xml:space="preserve">Abstract</x> Objective To assess the efficacy and tolerability of eletriptan in treating migraine attacks occurring within the defined menstrual time period of 1 day before and 4 days after onset of menstruation (menses days –1 to +4) compared with attacks occurring during non‐menstrual time periods (occurring outside of menses days –1 to +4). Background Migraine attacks during menses have been associated with longer duration, higher recurrence rates, greater treatment resistance, and greater functional disability than those not associated with menses. The efficacy of eletriptan in treating migraine attacks associated with menstruation vs those outside a defined menstrual period has not been evaluated. Methods Data were pooled from 5 similarly designed, double‐blind, randomized, placebo‐controlled trials of eletriptan 20 mg/40 mg/80 mg. Two groups were defined for this analysis: women with a single index migraine beginning during the menstrual (group 1) and non‐menstrual (group 2) time periods. End points of interest were headache response at 2 hours, migraine recurrence and sustained responses for nausea, photo/phonophobia, and function. Logistic regression was used to compare group 1 vs group 2 and each eletriptan dose (20, 40, or 80 mg) vs placebo. Adverse events were also assessed. Results Of 3217 subjects pooled from 5 studies, 2216 women were either in group 1 (n = 630) or group 2 (n = 1586). Rates of headache response at 2 hours were similar in group 1 vs group 2 (odds ratio [OR] = 1.11 [95% confidence interval (CI) 0.91, 1.36]; P = .2944). The rate of headache recurrence was significantly higher in group 1 vs group 2 (26.8% vs 18.6%; OR = 1.67 [95% CI 1.23, 2.26]; P < .001). The odds of achieving sustained nausea responses were significantly lower in group 1 than in group 2 (OR = 0.70 [95% CI 0.54, 0.92]; P = .0097). There was no significant difference between group 1 and group 2 in the odds of achieving a sustained photo/phonophobia and functional response (OR = 0.96 [95% CI 0.77, 1.20]; P = .7269 and OR = 1.14 [95% CI 0.87, 1.50]; P = .3425, respectively). Adverse events were comparable between group 1 and group 2. Conclusions Two‐hour headache outcome measures were similar in women treated with eletriptan both within and outside of the defined menstrual time period (menses days –1 to +4). The main treatment differences between the 2 groups occurred 2‐24 hours post‐treatment, with higher recurrence rates and lower sustained response rates for nausea in the group treated during the menstrual time period.